Laminar burning velocities of benzene + air flames at room and elevated temperatures. (1st July 2016) - Soloviova – Sokolova, J.V.; Alekseev, V.A.; Matveev, S.S.; Chechet, I.V.; Matveev, S.G.; Konnov, A.A.
Highlights: The burning velocities of benzene + air flames at several temperatures were measured. Comparison of predictions of 3 mechanisms with the experimental data showed mixed agreement. The temperature dependence of the burning velocity was interpreted using an empirical power law. Detailed model from Politecnico di Milano performs the best over the range of conditions studied. Abstract: Laminar burning velocities, S L, of benzene + air flames were determined at atmospheric pressure and initial gas temperatures, T, of 298, 318, 338 and 358 K. Non-stretched flames were stabilized on a perforated plate burner using the heat flux method. New measurements were compared with available literature results obtained in spherical and counterflow flames at room and elevated temperatures. Data consistency was assessed with the help of analysis of the temperature dependence of the laminar burning velocity, which was interpreted using an empirical expression S L  =  S L0 ( T / T 0 ) α . Both the laminar burning velocities and the power exponents, α, were compared with predictions of three kinetic mechanisms: JetSurF 2.0, and two models for kerosene developed at Politecnico di Milano: Skeletal Surrogate (121 species) and high-temperature detailed (ver. 1412). The last model demonstrated the best performance over the range of conditions studied.